A new fossil Saldidae (Hemiptera: Heteroptera: Leptopodomorpha) from the Early Cretaceous in China - Zhang, Weiting; Song, Jingjing; Yao, Yunzhi; Ren, Dong (Zootaxa, 2012)
Venustsalda locella gen. et sp. nov. is described and illustrated from the Lower Cretaceous Yixian Formation at Huang-banjigou Village, Liaoning Province, China. The new genus is established based on its unusual six cells on the membrane, with the second cell smallest.